Characteristics of Acquirers and Targets in Domestic and Cross‐border Mergers and Aquisitions. Issue 3 (17th July 2013) - Liu, Qing; Qiu, Larry D.
Abstract To help understand mergers and acquisitions (M&As), this paper utilizes the most recent M&A data (1991–2007) to establish empirical facts on a variety of performance measures for M&A acquirers, targets, and non‐participants. Unlike the finance literature which mainly focuses on abnormal returns, our performance measures include firm size, technology, productivity, and profitability. Generally, in domestic M&As, in cross‐border M&As, in the pre‐merger period and in the post‐merger period, acquirers perform better than targets, whereas targets perform better than non‐participants. Firms' performance is improved after the M&As. We also find that in the pre‐merger period, US firms that acquire foreign firms in developing countries are significantly better than those that acquire foreign firms in developed countries.